The BrainHealth Project study protocol: a scalable digital approach to measuring and promoting multidimensional brain health across the lifespan - Cook, Lori G.; Spence, Jeffrey S.; Venza, Erin E.; Tate, Aaron; Robertson, Ian H.; D’Esposito, Mark T.; Ling, Geoffrey S. F.; Wigginton, Jane G.; Chapman, Sandra Bond (Frontiers in Human Neuroscience, 2025)
BackgroundOptimization of brain health is a focal point in medical science, yet data regarding measuring, improving, and preserving lifelong brain health are lacking. This void demands an objective, change-sensitive measure of brain health and proven strategies to strengthen brain performance. The BrainHealth Project addresses these key issues, drawing upon neuroplasticity evidence of persistent modifiability of brain function across the lifespan. This landmark study aims to (i) evaluate and refine multidimensional change indices of brain health, (ii) evaluate the impact of evidenced-based cognitive strategies and lifestyle interventions on improving/maintaining brain health, and (iii) elucidate the mechanisms associated with brain health gains/losses.MethodsThis quantitative, longitudinal, interventional, open-label, single-arm clinical trial aims to recruit 100,000 generally healthy adults ages 18–100 and evaluate changes for 10 years or longer. Assessments, coaching, and training are conducted online through the secure BrainHealth Platform, allowing utilization tracking. The BrainHealth Index (BHI) – a multidimensional assessment – is offered at baseline and every 6 months. Participants have access to coaching every 3 months and continual access to self-paced trainings and resources. The primary outcome is the composite BrainHealth Index score and its empirically derived subdomain scores: Clarity (cognitive health), Connectedness (social health), and Emotional Balance (mental health). The BHI includes validated measures sensitive to change, including gains or losses associated with behavior change and integration of cognitive strategies into daily life. This Index contrasts with traditional assessments focused primarily on detecting cognitive decline or diagnosing pathological conditions, yet it, too, has been found to be sensitive to small incremental losses. The primary online training, SMART (Strategic Memory Advanced Reasoning Tactics), is a strategy-based program validated with 25+ years of research. SMART promotes improvements in neural health, cognition, wellbeing, connectedness, and real-life function, previously reported in randomized controlled trials (RCTs). Statistical approaches focus on individual prediction using nonlinear models trained with large samples and on assessing mechanisms influencing gains or losses on brain health metrics.DiscussionThis research extends prior RCT evidence to a longitudinal, epidemiologic approach, leveraging digital health and machine learning tools to deliver a generalizable measure of longitudinal brain health and actionable ways to achieve precision brain health. By integrating advanced statistical methods and large-scale data, the BrainHealth Project aims to provide medicine and society with accurate, multidimensional, sensitive, and actionable ways to optimize brain health practices across the lifespan.